2022
DOI: 10.1007/s00701-022-05406-4
|View full text |Cite
|
Sign up to set email alerts
|

Unlike severe periodontitis, caries does not associate with intracranial aneurysms or aneurysmal subarachnoid hemorrhage

Abstract: Purpose Periodontal diseases and caries are common oral diseases that predispose to tooth loss if untreated. In this study, we investigated whether loss of teeth or caries associate with intracranial aneurysm (IA) pathology similar to periodontal diseases. Methods A total of 166 patients with either IA or aneurysmal subarachnoid hemorrhage (aSAH) underwent oral examination in Kuopio University Hospital and Tampere University Hospital. Findings were compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Hallikainen et al [ 76 ] found that periodontitis was significantly associated with IAs and significantly increased the risk of SAH, while caries did not [ 78 ]. The association of periodontitis with the risk of IA formation and SAH was independent of gender, smoking status, hypertension, or alcohol abuse.…”
Section: The Oral Microbiome and Intracranial Aneurysm Formation And ...mentioning
confidence: 99%
“…Hallikainen et al [ 76 ] found that periodontitis was significantly associated with IAs and significantly increased the risk of SAH, while caries did not [ 78 ]. The association of periodontitis with the risk of IA formation and SAH was independent of gender, smoking status, hypertension, or alcohol abuse.…”
Section: The Oral Microbiome and Intracranial Aneurysm Formation And ...mentioning
confidence: 99%
“…First, IAs share a high degree of risk factors with PD, including smoking and obesity [ 15 ]. Second, multiple case-control studies of patients with IAs have shown that periodontitis is independently and positively associated with the risk of IAs and aneurysmal subarachnoid hemorrhage (aSAH)[ 16 , 17 ]. For example, periodontitis (≥ 4 mm gingival pockets) and severe periodontitis (≥ 6 mm gingival pockets) were seen in 92% and 49% of patients with IAs, respectively, and were associated with IAs (OR 5.3, 95% CI 1.1–25.9, p < 0.000; OR 6.3, 95% CI 1.3–31.4, p < 0.001) [ 16 ].…”
Section: Introductionmentioning
confidence: 99%